Docosahexaenoic acid attenuates hyperglycemia-enhanced hemorrhagic transformation after transient focal cerebral ischemia in rats. (20th August 2015) - Lin, Y.; Xu, M.; Wan, J.; Wen, S.; Sun, J.; Zhao, H.; Lou, M.
Highlights: DHA attenuates hyperglycemia-enhanced HT after focal ischemic injury. DHA reduces infarct volume and improves neurological outcome. DHA inhibits inflammatory reaction and stabilizes the blood–brain barrier. Abstract: Hemorrhagic transformation (HT) is a feared complication of cerebral ischemic infarction, especially following the use of thrombolytic therapy. In this study, we examined whether docosahexaenoic acid (DHA; 22:6n-3), an omega-3 essential fatty acid family member, can protect the brain from injury and whether DHA can decrease the risk of HT enhanced by hyperglycemia after focal ischemic injury. Male Sprague–Dawley rats were injected with 50% dextrose (6 ml/kg intraperitoneally) to induce hyperglycemia 10 min before 1.5 h of filament middle cerebral artery occlusion (MCAO) was performed. Treatment with DHA (10 mg/kg) 5 min before reperfusion reduced HT and further improved the 7-day neurological outcome. It also reduced infarct volume, which is consistent with the restricted DWI and T2WI hyperintensive area. Reduced Evans Blue extravasation and increased expression of collagen IV indicated the improved integrity of the blood–brain barrier (BBB) in DHA-treated rats. Moreover, DHA reduced the expression of the intercellular adhesion molecule-1 (ICAM-1) in the ischemic injured brain. Therefore, we conclude that DHA attenuated hyperglycemia-enhanced HT and improved neurological function by preserving the integrity of BBB and reducing inflammation.